2024
DOI: 10.2147/opth.s457503
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Macular Fluid with Central Retinal Artery Occlusion and Anterior Ischemic Optic Neuropathy

Yousef Fouad,
Mohamed Hamza,
Moataz Wessam

Abstract: Purpose To examine the prevalence and distribution of fluid within a cohort of eyes with acute central retinal artery occlusion (CRAO) and non-arteritic anterior ischemic optic neuropathy (AION) using optical coherence tomography (OCT). Methods A retrospective analysis of patient records and OCT imaging. Patients presenting with acute CRAO or AION who had available macular OCT imaging and no co-morbidities known to cause macular fluid were included in the analysis. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…
We read with interest the article by Fouad et al regarding macular fluid in CRAO and AION. 1 The results obtained in 11 cases of AION are generally in agreement with the acute phase findings in our own study, 2 emphasizing that early OCT imaging is crucial to detect retinal fluid accumulation and tissue oedema in AION. However, we disagree with the comment that in our article we reported that the finding in the inner nuclear layer (INL) of microcystic macular oedema (MME) "constitutes inner retinal cysts presumably associated with impaired axonal transport".
…”
supporting
confidence: 86%
“…
We read with interest the article by Fouad et al regarding macular fluid in CRAO and AION. 1 The results obtained in 11 cases of AION are generally in agreement with the acute phase findings in our own study, 2 emphasizing that early OCT imaging is crucial to detect retinal fluid accumulation and tissue oedema in AION. However, we disagree with the comment that in our article we reported that the finding in the inner nuclear layer (INL) of microcystic macular oedema (MME) "constitutes inner retinal cysts presumably associated with impaired axonal transport".
…”
supporting
confidence: 86%
“…
We thank Plant et al for their interest in our article "Prevalence and Distribution of Macular Fluid with Central Retinal Artery Occlusion and Anterior Ischemic Optic Neuropathy". 1 In our study, 6 out of 11 eyes with acute non-arteritic anterior ischemic optic neuropathy (AION) had intraretinal fluid on optical coherence tomography (OCT). All 6 eyes had fluid involving the outer nuclear layer, 4 eyes had fluid within the inner nuclear layer (INL), and 3 eyes had fluid within the ganglion cell layer (GCL).We agree with the authors of the letter on the importance of distinguishing the acutely developing microcystic macular edema from the later developing cystic degeneration of the INL (referred to as "retrograde maculopathy").
…”
mentioning
confidence: 84%